The Determinants of Dividend Payout: Evidence from the Malaysian Property Market - Chun Lin, Ong; Mohd Thas Thaker, Hassanudin; Khaliq, Ahmad; Mohd Thas Thaker, Mohamed Asmy (IQTISHADIA, 2018)
The paper aims to investigate the determinants of dividend payout among the Malaysian property companies. The sample size consists of 30 property listed companies on Bursa Malaysia. The data are generally obtained from the company’s annual report for the period of 2012 to 2016. The study employs multiple regression analysis to examine the influence of firms specific and macroeconomic variables on dividend payout. Result of the test shows that the dividend payout has a significant negative relationship with ownership structure and positive relationship on return on equity, quick ratio and GDP. The study instigates to enrich the literature on dividend determinants especially in the context of Malaysia.